2015
DOI: 10.1007/s10068-015-0107-y
|View full text |Cite
|
Sign up to set email alerts
|

Functional properties of protein isolates from different pea cultivars

Abstract: Surface characteristics and functional attributes of protein isolates prepared from different pea cultivars using isoelectric precipitation were investigated. Protein levels of isolates ranged from 81-89% with isoelectric points occurring between pH 4.7-4.9. Surface hydrophobicity values differed among cultivars with CDC Dundurn and CDC Striker isolates having the lowest and highest values, respectively. Protein solubility values at pH 7.0 varied with MFR042 and CDC Dundurn isolates displaying the lowest (appr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
60
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 81 publications
(72 citation statements)
references
References 31 publications
6
60
1
Order By: Relevance
“…OHC. Although no cultivar differences were observed by Stone et al (2015a) among seven pea cultivars tested, the authors reported lower OHC means (1.1-1.4 g/g). Therefore, all data were analyzed as a function of cultivar irrespective of environment.…”
Section: Resultsmentioning
confidence: 68%
See 2 more Smart Citations
“…OHC. Although no cultivar differences were observed by Stone et al (2015a) among seven pea cultivars tested, the authors reported lower OHC means (1.1-1.4 g/g). Therefore, all data were analyzed as a function of cultivar irrespective of environment.…”
Section: Resultsmentioning
confidence: 68%
“…The mean solubility of the PPIs ranged from 62.5 to 75.2%. Stone et al (2015a) also found significant differences in nitrogen solubility among seven pea cultivars tested, with means of 54-76%. Overall, the nitrogen solubility of isolates produced from pea grown at Rosthern in 2012 (mean = 71.6%) was higher than those prepared from pea grown in other environments (range = 67.6-67.8%).…”
Section: Resultsmentioning
confidence: 77%
See 1 more Smart Citation
“…Numerous plant-based proteins have been shown to be promising emulsifiers, including pea proteins [13], lupin proteins [14], soy proteins [15], and corn germ proteins [16]. The major challenges in this area are (i) identification of economically viable protein sources; (ii) establishment of effective methods for protein isolation, fractionation and purification; (iii) characterization of emulsifier functionality in terms of emulsion formation and stability.…”
Section: Overview Of Natural Food-grade Emulsifiers Proteinsmentioning
confidence: 99%
“…High-pH solution is used to separate most proteins from raw materials, and then isoelectric point precipitation is used to obtain protein isolate (Panpipat & Chaijian, 2016). It has been demonstrated that isoelectric point dissolution/precipitation can produce functional proteins from aquatic and terrestrial species, such as rainbow trout byproduct (Tahergorabi, Beamer, Matak, & Jaczynski, 2012), bigeye snapper (Priacanthus tayenus) head byproduct (Panpipat & Chaijan, 2017), beef heart (Mireles Dewitt, Gomez, & James, 2002), and pea (Stone, Avarmenko, et al, 2015).…”
mentioning
confidence: 99%